The Renin-Angiotensin System Modulates Inflammatory Processes in Atherosclerosis: Evidence from Basic Research and Clinical Studies. (14th April 2009) - Montecucco, Fabrizio; Pende, Aldo; Mach, François
Abstract : Recent evidence shows that the renin-angiotensin system is a crucial player in atherosclerotic processes. The regulation of arterial blood pressure was considered from its first description of the main mechanism involved. Vasoconstriction (mediated by angiotensin II) and salt and water retention (mainly due to aldosterone) were classically considered as pivotal proatherosclerotic activities. However, basic research and animal studies strongly support angiotensin II as a proinflammatory mediator, which directly induces atherosclerotic plaque development and heart remodeling. Furthermore, angiotensin II induces proatherosclerotic cytokine and chemokine secretion and increases endothelial dysfunction. Accordingly, the pharmacological inhibition of the renin-angiotensin system improves prognosis of patients with cardiovascular disease even in settings of normal baseline blood pressure. In the present review, we focused on angiotensin-convertingenzyme (ACE) inhibitors, angiotensin II receptor blockers (ARBs), and renin inhibitors to update the direct activities of the renin-angiotensin system in inflammatory processes governing atherosclerosis.